Analisis Pengendalian Kualitas Produksi D21N Inner Lens - Dewi Susanti; Nofriani Fajrah (Prosiding, 2020)
The technology competition in the industry today is very tight. Companies that maintain product quality and improve product quality according to customer requirements. Therefore, in the process of producing the Reflector and Inner Lens, there are several obstacles that often occur in the production process, namely defects in the bubble, silver, and white dot. This study aims to identify the disabilities that often occur if well controlled, to determine the factors that cause these disabilities. Fishbone diagrams are used to identify factors that cause defects. There are 4 factors that cause defects based on the fishbone diagram, namely human, machine, environmental and material factors. The results showed that there was no data out of control. The dominant defect types in D21N Inner Lens products are bubbles (53.5%) and silver 760 Reflector A products (69.7%).